Analisis Tren Indikator Pendidikan dan Pengeluaran per-Kapita Kalimantan Timur 2020-2025 - Muhammad Nabil Rahmatullah; Jovan Bagas Pangestu; Alya Mayasha; Aulia Natasya; Sifwah Fatin Sofwani; Muhammad Riva Fachrodhiya; Rajiansyah Rajiansyah; Fahrul Agus (Buletin Ekonomika Pembangunan, 2026)
Human development and economic welfare are the two main pillars in the progress of a region. This study aims to analyze trends in education indicators, including Expected Length of School (HLS) and Average School Length (RLS), as well as their relationship with Per Capita Expenditure in East Kalimantan Province for the period 2020-2025. This topic was raised because there is a consistent gap between expectations and realization of education that can affect economic productivity. The novelty of this study lies in the use of recent time-series data covering the post-2020 recovery period, providing strong  evidence for policymakers. This research method uses a quantitative descriptive approach and simple linear regression analysis with data sources from the Central Statistics Agency (BPS) of East Kalimantan. The results of the study showed a significant positive trend, where RLS grew by 3.38% and Per Capita Expenditure grew by 21.54% during the observation period. The main findings show a very strong correlation (r=0.989) between education and the economy, where the regression model estimates that every 1-year increase in average school length is associated with an increase in per capita expenditure of Rp7.94 million. In conclusion, the acceleration of education realization has direct implications for increasing people's purchasing power. Therefore, the strategy of accelerating compulsory learning is crucial to boost the regional economy. Keywords: Education Indicators; Development Economics; Human Capital;      Expenditure per Capita; East Kalimantan